Heatwaves cause fluctuations in wMel Wolbachia densities and frequencies in Aedes aegypti. - Perran A Ross; Jason K Axford; Qiong Yang; Kyran M Staunton; Scott A Ritchie; Kelly M Richardson; Ary A Hoffmann (Public Library of Science (PLoS), 2020)
Aedes aegypti mosquitoes infected with the wMel strain of Wolbachia are being released into natural mosquito populations in the tropics as a way of reducing dengue transmission. High temperatures adversely affect wMel, reducing Wolbachia density and cytoplasmic incompatibility in some larval habitats that experience large temperature fluctuations. We monitored the impact of a 43.6°C heatwave on the wMel infection in a natural population in Cairns, Australia, where wMel was first released in 2011 and has persisted at a high frequency. Wolbachia infection frequencies in the month following the heatwave were reduced to 83% in larvae sampled directly from field habitats and 88% in eggs collected from ovitraps, but recovered to be near 100% four months later. Effects of the heatwave on wMel appeared to be stage-specific and delayed, with reduced frequencies and densities in field-collected larvae and adults reared from ovitraps but higher frequencies in field-collected adults. Laboratory experiments showed that the effects of heatwaves on cytoplasmic incompatibility and density are life stage-specific, with first instar larvae being the most vulnerable to temperature effects. Our results indicate that heatwaves in wMel-infected populations will have only temporary effects on Wolbachia frequencies and density once the infection has established in the population. Our results are relevant to ongoing releases of wMel-infected Ae. aegypti in several tropical countries.